Characterization of residual soil properties on slope in Dusun UTM, Johor - Norhidayah, Mohamed; Muhammad Farhan, Zolkepli; Ahmad Safuan, A. Rashid; Muhammad Syamsul Imran, Zaini; Mohd Fakhrurrazi, Ishak (Semarak Ilmu Publishing, 2025)
The actual characterization of residual soil differs across different countries. Any soil that has remained at the original site without having moved is often referred to as residual soil. In order to design geotechnical structures that are simultaneously safe and cost-effective, including slope stability, it is essential to have a solid understanding of the characteristics of the residual soil. This understanding provides valuable insights regarding the behaviours and strength of the soil. One of the most common catastrophes that can take place in any part of the world, including Malaysia, is caused by a slope failure. Due to the high occurrence of accidents resulting from slope failure, it is necessary to conduct extensive scientific research aimed at identifying the precise characteristics of the soil at Dusun UTM, Johor. Numerous laboratory works have been carried out relating to the soil's index of physical properties and engineering properties. In terms of the properties of the residual soil, the area can be characterized as sandy silt with a significant level of plasticity. Result for consolidated isotropic undrained (CIU) test indicates that the stress-strain curve demonstrates a hardening behaviour, which no peak stress observed during shearing process. Moreover, increasing confining pressures applied to the soil sample led to enhancement in the soil’s strength properties. These findings provide valuable insights into the soil’s behavior, which can inform strategies for improving slope stability and mitigating risks associated with slope failure.